Those of women of Coromandel : a novel - Ranga Rao (Aleph Book Company, New Delhi, 2022)
Those Women of theCoromandel brings to life the eclectic, intertwined lives of three women living in Coromandel in nineteenth-centuryIndia. We meet Miss Beston who is known as the Boat Woman, a Briton who hasgone native. Living in her boat (that grows into a chain of houseboats, eachhousing a different area of her living and working quarters) she is anentrepreneur, hunter, and host and guide to every British official who passes throughthe Coromandel. Deeply interested in local culture, she befriends people aroundher, both Indian and British. Appachchi, known as Granny, is a lover of nature, mangoes, and the monsoon. An early encounter with a spiritual man, the Guru ofthe Stream, guides her to a divine understanding that underpins her life.Worker Aunt, Appachchi's sister-in-law, who endures successive personaltragedies with the utmost dignity, is her close confidante and lifelongbuttress. Also deeply influenced by the teachings of the Guru of the Stream, she undertakes a trip to Kasi later in life that establishes her as a spiritualfulcrum for the villagers. Peopledwith characters who are eccentric, interesting, and pragmatic, such as thescholarly BA Garu, Appachchi's husband and Worker Aunt's brother; Mr Blotton, the Brahma of the Godavari anicut; Nephew, the first to welcome the Guru of theStream, and others, Those Women of the Coromandel is a story of peopletrying to find their place in the world as it turns and changes around them.
Keywords: Indic fiction; Historical Fiction